Case Report: Ultralow-field portable MRI improves the diagnosis of congenital hydrocephalus - Groteklaes, Anne; Dresbach, Till; Born, Markus; Mueller, Andreas; Sabir, Hemmen (Frontiers in Pediatrics, 2025)
IntroductionCongenital hydrocephalus is an increasing condition both in high as in low and middle income countries. Main causes include aqueductal stenosis, neonatal central nervous system infections, intracranial hemorrhage, malformations and tumors. Investigation of its etiology should include magnetic resonance imaging (MRI) to detect especially pathologies of the fossa cranii posterior. However, MRI is not available to every infant presenting with congenital hydrocephalus especially in those countries with the highest prevalence. New portable ultralow-field MRI (ULF) allows low resource and bedside imaging and thus widens the access to MRI for those infants. This study presents two cases of newborns with congenital hydrocephalus who underwent ULF scanning revealing a tumor of the fossa cranii posterior as cause of hydrocephalus. This study shows that ULF scanning allows to detect and characterize brain tumors as well as metastases.Setting and patientsIn this case report, we present two cases of newborns antenatally diagnosed with hydrocephalus with no further pathology detected in repeated cranial ultrasound and, in one case, fetal MRI. We performed ULF imaging using a portable 0.064T MRI during natural sleep and high-field 3T MRI to investigate the etiology of congenital hydrocephalus in these infants.Main resultsULF imaging revealed a tumor of the fossa cranii posterior in both cases. MRI signalling detected in ULF imaging was specific for each tumor (ATRT, low grade glioma). In one case, ULF imaging also detected intracerebral metastasis.ConclusionsWe demonstrated that ULF imaging is able to detect tumors of the fossa cranii posterior that are not detected on ultrasound and shows their specific MR-signalling as well as detect metastasis. Additionally, compared to 3T MRI, ULF MRI was able to reveal significant findings while requiring fewer resources and being easier to perform. Therefore, we propose that children with congenital hydrocephalus not showing any abnormalities on cranial ultrasound should undergo ULF MRI. This imaging modality holds potential for monitoring neonatal tumors and detecting metastasis.